2023
DOI: 10.3390/jof9040448
|View full text |Cite
|
Sign up to set email alerts
|

Differential Recognition of Clinically Relevant Sporothrix Species by Human Mononuclear Cells

Abstract: Sporotrichosis is a human and animal fungal infection distributed worldwide that is caused by the thermodimorphic species of the Sporothrix pathogenic clade, which includes Sporothrix brasiliensis, Sporothrix schenckii, and Sporothrix globosa. The cell wall composition and the immune response against the Sporothrix species have been studied mainly in S. brasiliensis and S. schenckii, whilst little is known about the S. globosa cell wall and the immune response that its components trigger. Therefore, in this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 84 publications
0
2
0
Order By: Relevance
“…However, some variations were observed in the case of S. brasiliensis conidia, where the essential receptors are dectin-1 and TLR2, a result that could be related to the cell wall organization of this morphology ( Figure 10 ). 26 , 76
Figure 10 Phagocytosis and receptors involved in the immune recognition of different species of the Sporothrix pathogenic clade. Macrophages and dendritic cells can phagocytose yeast-like cells and conidia of S. schenckii, S. brasiliensis , and S. globosa.
…”
Section: Discussionmentioning
confidence: 99%
“…However, some variations were observed in the case of S. brasiliensis conidia, where the essential receptors are dectin-1 and TLR2, a result that could be related to the cell wall organization of this morphology ( Figure 10 ). 26 , 76
Figure 10 Phagocytosis and receptors involved in the immune recognition of different species of the Sporothrix pathogenic clade. Macrophages and dendritic cells can phagocytose yeast-like cells and conidia of S. schenckii, S. brasiliensis , and S. globosa.
…”
Section: Discussionmentioning
confidence: 99%
“…Next, we assessed the contribution of some pattern recognition receptors (PRRs) during the Sporothrix-PBMC interaction. We blocked dectin-1 with the antagonist laminarin [27] while blocking MR, CR3, TLR2, and TLR4 with monoclonal specific blocking antibodies [53,54]. The TNFα and IL-6 stimulation by the WT control strain was significantly affected by preincubation of human PBMCs with laminarin and anti-TLR2 and to a lesser extent by anti-TLR4 (Figure 5).…”
Section: The Gp70 Silencing Affected the Human Innate Immune Cell-spo...mentioning
confidence: 99%
“…Recently, the CW composition was analyzed in conidia, germlings, and yeast-like cells of S. globosa and compared with S. schenckii and S. brasiliensis . It was found that both conidia and yeast-like cells of S. globosa had a higher amount of chitin in their CWs, and all morphologies had more exposed β1,3-glucan on their surface compared to S. schenckii and S. brasiliensis [ 57 ]. The composition and structure of the fungal cell wall are influenced not only by environmental conditions but also by the cell cycle, changes in growth form, and other processes [ 58 , 59 , 60 , 61 ].…”
Section: Sporothrix and Sporotrichosismentioning
confidence: 99%